Using Pedagogical Improvisation In Preparing Music Teachers To Work With Children With Disabilities - Adiba Minggirovna Syomkina (Euro Asian Journal Publishing, 2024)
The relevance of music classes for children with disabilities lies in the fact that they allow each child, regardless of his abilities and talents, to discover and express himself, learn to understand and love songs and music, take part in concert activities, while overcoming certain physical disabilities and mental development. In this regard, we can highlight the positive role of music classes in improving the physical, moral and psychological state of children with disabilities, correcting existing deficiencies in the emotional-volitional sphere, developing aesthetic perception, etc
Keywords: students with disabilities; pedagogy; music